Role of procedures in environmental management system - Grzegorz Embros (Studia Ecologiae et Bioethicae)
In the paper, the author attempts to point out the meaning of procedures for the environmental management system (EMS). Particular attention is paid to form and content as well as to the functions, proprieties, and structure of the procedures. The analyses were carried out taking into account a systemic approach of the essential topics to the ISO 14001 standard. Based on the chosen procedure, some fundamental methods of elaborating upon and implementing the EMS procedures were outlined. It was also presented that procedures written in accordance with these rules might provide vital support to the improvement of the organization’s management systems and might optimize the processes in the areas they cover.